RELIABILITY OF THE AO CLASSIFICATION OF THORACOLUMBAR FRACTURES COMPARED TO TLICS AND MAGERL - MARQUES,CARLOS AUGUSTO COSTA (2017)
ABSTRACT Objective: To test the reliability of the new AO/2013 classification compared with AO/Magerl and TLICS. Methods: Four spine surgeons retrospectively and blindly evaluated imaging and clinical data from 98 patients with thoracolumbar fractures. Results: Using the Kappa coefficient, we obtained the best reproducibility for the AO/2013 classification compared to the other two, represented by Kappa coefficient of 0.690. We could also obtain, with good reproducibility among the evaluators (Kappa 0.690), the most common subtypes of AO/2013 classification with indication for surgery. Conclusion: We believe that the new AO/2013 classification has proven to be a good communication tool among spine surgeons with good reproducibility, but more studies should be conducted in several centers in order to be consolidated and so that the prognosis between the types of injury is better understood.